Diabetes Insipidus with Hypoxic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Neurogenic diabetes insipidus (DI) due to hypoxic encephalopathy is reported in 6 cases and 28 pediatric cases in the literature are reviewed from the Mackay Memorial Hospital, Taipei, Taiwan, ROC.